HUBUNGAN SOSIAL PATRON KLIEN ANTARA TAUKE SAWIT DAN PETANI SAWIT DI DESA MENGGALA TELADANKECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Syaputra, Ary; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The relationship between employer and smallholders here is the dependency relationship and interests, where oil palm farmers to borrow money from employer and the employer need of fresh fruit bunches (FFB) .where -masing each of them will preserve and maintain the existing relationship, this interest will guard it -baiknya, in safe guarding the interests of this they must respect the norm - the norm for the relationship that has been preserved is not damaged so saja.yang until eventually the relationship which was originally only for the benefit of and dependence over time turned into sosial.tujuannya relation to their interests.This type of research is a descriptive study using a quantitative approach. This research was conducted in the village of Menggala Exemplary, Tanah Putih, Rokan Hilir, with the sample by taking 10% of each patron, the number of samples in this study were 33 people.Results from this study is the patron-client relationship between employer palm smallholders Village Menggala Exemplary background with a relationship of mutual need and mutual dependence on each other, although in this relationship occurs imbalance between employer palm (patron) and smallholders (client) Exemplary however Menggala village patron-client relationship is constantly interwoven and never caused any problems or social conflicts. The elements that make up the patron-client relationship between employer palm oil growers village is Menggala Exemplary networks, trust and norms. The pattern forming patron-client relationship between employer palm smallholders Village Menggala Exemplary deliberate pattern of deliberately created to deal with competition among employer in the village Menggala Exemplary or from outside the village with smallholders which amounts to much because the majority of the village residents Menggala Exemplary is smallholders.Keywords: Takuke Oil (Patron), Smallholders (Client), Patron-client relations